The Effect of Learning with Bamboo Dancing Learning Methods on Biology Learning Outcomes of Students of IX SMP Negeri 1 Bambel on Biotechnology Materials - Halisah Suriani (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This study aims to determine the effect og using the Bamboo Dancing Learning Methods on the Biology learning outcomes of IX students of SMP Negeri 1 Bambel on biotechnology materials. Sample were taken 80 students from 104 students. The research design used in this study was one-group pre-test and post-test design. In collecting data, a multiple-choice biology learning outcome test was used. The data analysis technique in this study used the calculation of the mean, median, mode, and variance according to Sudjana’s theory and continued with the t-test. From the research that has been done on the bamboo dancing learing methoods, the average pre-test is 61,44, the median is 62,5 and the mode is 60, while the average post-test score on the post-test is 80,75, the median is 80 and the mode is 80. It can be seen that the student’s scores on the post-test were much higher than the pre-test scores, the t-count value was greater than the t-table (13,76>1,67), so Ho wa rejected and Ha was accepted. So, student learning outcomes after being given teaching with bamboo dancing methods increased, In other words: “there is an effect of using the bamboo dancing learning methods on student learning outcomes on the subject matter of biotechnology in class IX of SMP Negeri 1 Bambel.